Mitochondrial tRNAThr A15951G mutation may not be associated with Leber's Hereditary Optic Neuropathy. (3rd July 2016) - Zhang, Xi; Yu, Shuaishuai; Tu, Yunhai; Huang, Wenjie
Abstract: Mutation in mitochondrial DNA (mtDNA) has been found to play an important role in the pathogenesis of Leber's Hereditary Optic Neuropathy (LHON). Three primary mutations, the ND4 G11778A, ND6 T14484C, and ND1 G3460A, have been found to account more than 90% of LHON patients in many families worldwide. In addition to the mutations in genes encoding the respiratory chain complex I, reports concerning the mt-tRNA gene mutations associated with LHON have increased, some pathogenic mutations caused the failure in mt-tRNA metabolism, thereby worsened the mitochondrial dysfunction that is responsible for LHON. Recently, the A15951G mutation in mt-tRNA Thr gene has been reported to be a "modified" factor in increasing the penetrance and expressivity of LHON-associated ND4 G11778A mutation in three Chinese families. However, evolutionary conservation analysis of this mutation suggested a poor conservation index and the pathogenicity scoring system showed that this mutation was a neutral polymorphism.